Teenagers Poor Readers: Evaluation of Basic Cognitive Process - Rosa del Carmen Flores Macías; Juan Eugenio Jiménez González; Eduardo García Miranda (Universidad Autónoma de Baja California, 2015)
The present study aims to investigate the cognitive processes associated with reading difficulties of teenage poor readers. Several studies suggest that this population presents a poor comprehension, despite reading the words properly and have good phonological skills (which distinguishes them from a population with dyslexia). With a comparative cross-sectional design the Sicole-R multimedia battery, which assesses basic cognitive processes related to reading, was applied to participants. Results indicate that poor reader students exhibit a lower performance than normal readers in phonological awareness, orthographic processing and processing syntax, although only the latter comparison was statistically significant.